Comparison Analysis of Alfamart Customer Service Satisfaction and Progress With using Customer Satisfaction Index (CSI) and Service Quality (SQ) Methods - Johan Tanaro; Rudi Yanto; Putra Edi Mujahid (STMIK Budi Darma, 2021)
Currently, retail business competition in Indonesia is very tight, it is proven that it is easy to find retailers around, and in almost every region of Indonesia. To provide satisfaction to customers, companies must be able to sell goods or services of the best quality, at reasonable prices and improve service quality. This research was conducted by distributing 100 questionnaires and calculating using the Customer Satisfaction Index (Csi) method which aims to determine the overall level of customer satisfaction and then calculating the Service Quality (Sq) to determine the GAP value or the gap in customer perceptions and expectations. From the results of calculations using the Customer Satisfaction Index (Csi) MajuBersama method gets a score of 90.74%, which means that customers are very satisfied with MajuBersama's services and must continue to be maintained and improved for Alfamart to get a score of 78.32% indicating that the level of satisfaction Alfamart customers in general are in the satisfied category, which means there is one more level, namely the range of 81 to 100. So it can be said that the performance of Alfamart is good, but Alfamart must continue to improve the quality of service, especially on attributes whose service value is less than satisfactory and can maintain or improve attributes that are very important and very satisfying in order to increase satisfaction with Alfamartservices